Electrochemistry and morphology of graphite negative electrodes containing silicon as capacity-enhancing electrode additive. (10th October 2019) - Jeschull, Fabian; Surace, Yuri; Zürcher, Simone; Spahr, Michael E.; Novák, Petr; Trabesinger, Sigita
Abstract: In this study, the use of silicon as a capacity-enhancing electrode additive to graphite electrodes was investigated. Based on energy-density estimations, the silicon amount was restricted to less than 20 wt%. The viability of such graphite–Si electrode blends was evaluated with regard to their cycle-life in relation to the silicon content of the electrode, showing how Si content and capacity fade are correlated. The addition of Si gradually alters the electrode morphology as shown by electrode cross-section images, and is partly responsible for the progressive capacity loss. In addition, we also demonstrate how analysis of the voltage hysteresis can provide early indications of cell failure. To complete the picture, one graphite–Si formulation was evaluated in a full-cell setup. The electrochemical study of this 3-electrode setup is complemented by a charge-injection experiment that replenishes the Li inventory and serves to pinpoint the origins of capacity fading more accurately under the cycling conditions chosen. Graphical abstract: Image 1 Highlights: Energy density considerations for different Si content in anodes. Performance pitfalls of graphite electrodes with 5–20 wt% Si. Early indications of electrode breakdown by analysis of voltage hysteresis. Full-cell testing of a graphite:Si.||LFP battery Li-injection experiments in a 3-electrode setup.